Perlas - Rili, Ayne Kierulf 1978-; University of the Philippines Diliman College of Mass Communication (Quezon City College of Mass Communication, University of the Philippines Diliman, 2000)
Perlas is a story of pain, of greed, of revenge, of basic human nature, and of women. The story is relatively simple, there is nothing extraordinary about it. In fact, I'm sure everyone knows of a story, which is similar to the one portrayed in Perlas. This is because it happens all the time. Yet, the ways that the story has come together in the person of Pina in the short film Perlas, and the circumstances chosen to dress up the story presents for us a new perspective from which to view this age of old story of pain and suffering. The pain caused by the struggle against the constraints of society on women and the suffering caused by these constraints.
Vita.
Thesis (A.B. Film and Audiovisual Communication)--University of the Philippines Diliman
Keywords: Perlas (Short films -- Philippines).; Women -- Social and moral questions -- Philippines; Suffering in motion pictures -- Philippines